Rancang Bangun Sistem Informasi Persediaan Barang Dan Penjualan Pada Perusahaan Air Mineral Aura Water Di Jember Berbasis Web - Lofty Alvito Surya A; R.B. Moch Gozali; Muhammad Firdaus (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to design and develop a web-based inventory and sales information system to support operational activities, particularly at Aura Water, a mineral water company based in Jember, in a more effective and efficient manner. This research employs a qualitative method. In developing the system, the researcher uses the waterfall software development model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The system is developed using the PHP programming language with a MySQL database and is designed to ensure that the implemented features are user-friendly and easy to operate. The result of this research is an information system capable of automatically recording inventory data, sales transactions, and generating sales chart reports. With the implementation of this system, the company can monitor stock levels, sales traffic, transaction efficiency, and reduce the risk of recording errors. This system is expected to improve work efficiency and support more accurate decision-making for company management.